The Secret Of Skull Mountain - Dixon W. Franklin; Frankllin W. Dixon (Canada Franklin W. Dixon, 1948)
Frank and Joe Hardy investigate the mysterious overnight draining of Bayport's new reservoir. They discover a criminal syndicate, led by a villain named Kleng, is diverting the water to hide an illegal operation within a secret mountain tunnel, ultimately saving the town.
Keywords: courage, persistence, and proactive problem-solving in the face of crisis; courage, perseverance, and the importance of teamwork in overcoming adversity